Minutes of Joint Conference of the General Council of the Trades Union Congress, National Executive Committee of the Labour Party, and Executive Committee of the Parliamentary Labour Party - Labour Party (Great Britain)
1936-09-09 105. PRIVATE AND CONFIDENTIAL. G.C. 19. 1935-36. 9th September, 1936. TRADES UNION CONGRESS GENERAL COUNCIL MINUTES OF JOINT CONFERENCE HELD AT THE ROYAL HOTEL, PLYMOUTH, ON 9TH SEPTEMBER, 1936, AT 8 P.M. PRESENT: The General Council of the Trades Union Congress. National Executive Committee of the Labour Party. Executive Committee of the Parliamentary Labour Party. Mr. W. Stevenson, Editor of the "Daily Herald" was also present. 261. SPAIN REPORT FROM DELEGATION TO PARIS. Mr. George Hicks, M.P., Dr. Dalton, M.P., and Mr. Gillies gave a report on their visit to the French Socialists and Trade Unionists which had been undertaken to elicit the exact position with regard to the attitude they were now taking on non-intervention in Spain. Sir Walter Citrine read a statement issued that day by the Confederation General du Travail. The recommendations made by the delegation were fully discussed. Reply from the Foreign Office to the telegram sent fron Plymouth regarding the International Committee of Co-ordination, was read. After a full discussion, IT WAS DECIDED, on the motion of Mr. Bevin, to reaffirm the policy of the Joint Executives, adopted at the Transport Hall meeting, held on 28th August, 1936, and thank the delegation for their report. The motion was carried nom. con. (Mr. Morrison abstaining from voting.) 262. PROCEDURE - AT CONGRESS. Mr, Lawther suggested that the debate should take place at Congress and then the Unions should be given an opportunity to consult before the vote was taken. It was understood that the emergency resolution on Spain (see Minute 264) for the Congress would be drafted and printed that night for distribution to the delegates, reaffirming the policy of the Labour Movement, in the light of the discussion. Mr. Bevin moved, "That a statement be made to Congress that in view of the menace of Fascism to Democracy, and the present position that has developed, the whole question affecting the international situation should 292/946/10/106(i)